Analisis Variabel-Variabel yang Mempengaruhi Pendapatan Asli Daerah Provinsi Bali - Wulandari, Pande Paramitha; Ayuningsasi, Anak Agung Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 3, No. 11, November 2014 (pp.485-548), 2014)
One measure of the ability of a district to implement autonomy is achieved mainly PAD district. PAD is a reception area that is derived from natural economic resources area. This study aims to determine the effect of per capita income, inflation, investment, and regional autonomy and partial simultaneously against PAD Bali Province. Research carried out in the Province of Bali with the method of data collection that is non partisipan.Teknik observation data analysis using multiple linear regression analysis. The analysis showed that the per capita income, inflation, investment, and influential regional autonomy simultaneously against PAD Bali Province. Capita income and investment is positive and significant impact on PAD Bali Province, while the inflation rate and a significant negative effect on PAD Bali Province and variable regional autonomy is not a positive and significant effect on PAD Bali Province.
Keywords: original income areas; per capita income; inflation; investment; and regional autonomy